2005
DOI: 10.1097/01.mlg.0000179174.32345.41
|View full text |Cite
|
Sign up to set email alerts
|

Voice Disorders in the General Population: Prevalence, Risk Factors, and Occupational Impact

Abstract: The results of this large epidemiologic study provide valuable information regarding the prevalence of voice disorders, factors that contribute to voice disorder vulnerability, and the functional impact of voice problems on the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
527
10
26

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 663 publications
(624 citation statements)
references
References 9 publications
(11 reference statements)
31
527
10
26
Order By: Relevance
“…The occurrence of vocal symptoms in this sample was comparable to the occurrence in prevalence studies regarding voice disorders (Coyle et al, 2001;Roy, Merrill, Thibeault, Parsa, Gray, & Smith, 2004;Roy et al, 2005;Lyberg Åhlander, Rydell, Fredlund, Magnusson, Wilén, 2015). The descriptive data showed that vocal symptoms were more common among women, which is in line with previous findings (see for example Coyle et al, 2001;Roy et al, 2004;Wilson, Deary, Scott & MacKenzie, 1995).…”
Section: Gender Differencessupporting
confidence: 55%
See 1 more Smart Citation
“…The occurrence of vocal symptoms in this sample was comparable to the occurrence in prevalence studies regarding voice disorders (Coyle et al, 2001;Roy, Merrill, Thibeault, Parsa, Gray, & Smith, 2004;Roy et al, 2005;Lyberg Åhlander, Rydell, Fredlund, Magnusson, Wilén, 2015). The descriptive data showed that vocal symptoms were more common among women, which is in line with previous findings (see for example Coyle et al, 2001;Roy et al, 2004;Wilson, Deary, Scott & MacKenzie, 1995).…”
Section: Gender Differencessupporting
confidence: 55%
“…It is well established that voice disorders occur significantly more often among women than among men (Coyle, Weinrich, & Stemple, 2001;Herrington-Hall, Lee, Stemple, Niemi & McHone, 1988;Roy, Merrill, Gray & Smith, 2005). Dietrich et al (2008) concluded that individual differences seem to play a role in the evolvement of stress in persons with voice disorders and that these differences may to some extent be related to gender.…”
Section: The Role Of Gender In Voice Cortisol and Stressmentioning
confidence: 99%
“…Recently published data suggest that very few teachers in Swedish schools have undergone any voice training and that voice amplification is rare, even in the schools' sports halls 1 . As pointed out by many authors, teachers are at risk of developing voice problems and there is a high prevalence of voice disorders in teaching staff also when compared to other occupations with vocal demands [3][4][5][6] . Teachers' vocal load is also indicated by self-reported sick-leave due to voice problems.…”
Section: Introductionmentioning
confidence: 99%
“…[ Pain and discomfort during the last 2 weeks -yes; Age ->40; The longest occupation -manual 1 Node n(%); node number, % to 3,600 2 Gain n(%); gain number, % to 239 3 Response (%): The fraction of the self-reported voice problem in subjects 4 Gain index (%):=273.4 in total 5 node [ …”
Section: 서론mentioning
confidence: 99%